2016
DOI: 10.3390/molecules21111419
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol Exerts Anti-Obesity Effects in C57BL/6 Mice through Modulating Adipogenic Proteins and Gut Microbiota

Abstract: Obesity is a global health concern. Piceatannol (Pic), an analog of resveratrol (Res), has many reported biological activities. In this study, we investigated the anti-obesity effect of Pic in a high-fat diet (HFD)-induced obese animal model. The results showed that Pic significantly reduced mouse body weight in a dose-dependent manner without affecting food intake. Serum total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL) levels, and blood glucose (GLU) were significantly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 31 publications
0
75
0
2
Order By: Relevance
“…Genomic DNA was extracted from fecal samples using the innuSPEED Stool DNA kit (Analytik Jena AG) and following manufacturer's instructions. The primer sequences to amplify the V4 region of 16S rDNA was obtained from a previous study and the PCR conditions were refered by our previously reported . Then, the second Index PCR using the Illumina DNA library preparation kit (Illumina, San Diego, CA, USA) to construct the dual‐index barcodes and sequencing adaptors under the following conditions: 95°C for 3 min, 8 cycles of 95°C (30 s), 55°C (30 s), and 72°C (30 s), with a final extension at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from fecal samples using the innuSPEED Stool DNA kit (Analytik Jena AG) and following manufacturer's instructions. The primer sequences to amplify the V4 region of 16S rDNA was obtained from a previous study and the PCR conditions were refered by our previously reported . Then, the second Index PCR using the Illumina DNA library preparation kit (Illumina, San Diego, CA, USA) to construct the dual‐index barcodes and sequencing adaptors under the following conditions: 95°C for 3 min, 8 cycles of 95°C (30 s), 55°C (30 s), and 72°C (30 s), with a final extension at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…1,12 Resveratrol has also been shown to induce unique microRNA that trigger anti-inflammatory pathways as well as induce myeloid-derived suppressor cells (MDSCs). 1,7,8,13 While resveratrol has been shown to alter the gut microbiome in various disease models, [14][15][16][17] these studies have captured only an association between resveratrol-induced modulations in gut microbiota and the disease outcome. Thus, conclusive evidence, such as through fecal transfer, is lacking to connect resveratrolinduced modulation in gut microbiota and its beneficial effects against disease pathogenesis.…”
mentioning
confidence: 99%
“…Piceatannol effects on human health include improved insulin sensitivity, lower blood pressure, and heart rate in overweight men [79]. The supplementation of piceatannol in animals fed a high-fat diet showed a hypolipidemic effect, lowering total cholesterol, LDL cholesterol and atherogenic index [80], and also anti-obesity [81] when compared to animals in the same diet without piceatannol supplementation.…”
Section: Piceatannol In B Cydoniifolia Pulp and Seedmentioning
confidence: 99%